Reshaping higher educational institutions through frugal open innovation - Jayamalathi Jayabalan; Magiswary Dorasamy; Murali Raman (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Many private higher educational institutions (PHEI) are facing poor profitability, increased short term debts with under-resourced cash flow and insufficient funds that could lead to financial distress. To address the issues of ever-changing business environments and to deliver value propositions, PHEI should focus on their intangible assets to increase their capabilities to achieve frugal open innovation. The objective of this paper is to investigate the challenges faced by private universities from the practitioners' points of view and offer a practical solution. This paper also attempts to identify whether there is a need for any changes in business model or operations required by private universities to sustain their competitive advantage in the current environment. This study is exploratory in nature due to scarcity of past literature on frugal open innovation in PHEI context. Interviews were conducted with experienced practitioners to elicit their experience managing challenges in PHEI. As a result, this paper sheds light on the ability of PHEI to formalize, capture, and leverage its intangible assets rather than only investing and managing tangible assets in order to achieve frugal open innovation. Frugal open innovation is the enabler for PHEI to focus on core functions, create closer integration with industry, local and international communities and promote greater efficiency in operations. This paper is novel because it seeks to contribute to the current debate in the literature, positioning frugal open innovation (FOI) within the sphere of intellectual capital research, through exploring the effect of intellectual capital on frugal innovation is mediated through the information technology capability. The result indicates that sales and operating planning (S&OP) can be panacea for the five main challenges faced by PHEI includes structural challenges, operational challenges, financial challenges, social challenges and technological challenges. We conclude that there is a role for intellectual capital to achieve FOI by influencing IT capabilities, thus warrants more research to fill this research gap.
Keywords: 650; intellectual capital; frugal open innovation; open innovation dynamics; IT capabilities; higher education institution